Metabolomic profiling of Bacillus velezensis B13 and unveiling its antagonistic potential for the sustainable management of rice sheath blight - Naveena, Sirivella; Gopalakrishnan, Chellappan; Logeshwari, Rajendran; Raveendran, Muthurajan; Pushpam, Ramamoorthy; Lakshmidevi, Paranthaman (Frontiers in Plant Science, 2025)
Sheath blight disease is accountable for substantial loss in rice production worldwide. Endophytic bacteria are exploited as biocontrol agents due to their effectiveness in antagonizing a wide range of phytopathogens through a multifaceted approach. In the present study, the potentiality of deploying endophytic bacteria for the sustainable management of rice sheath blight was investigated. Over 40 bacterial endophytes were obtained and screened for their antagonistic activity against Rhizoctonia solani by a dual-culture assay. Among them, B. velezensis B13 exhibited higher mycelial inhibition (77.33%) against R. solani. A scanning electron microscopic study of the interaction of R. solani with B13 revealed distorted and deformed mycelia of R. solani. An analysis of secondary metabolites produced by B. velezensis B13 at their zone of interaction with R. solani confirmed the presence of various bioactive compounds of an antifungal and antimicrobial nature. A molecular docking study revealed that the compound 3′,8,8′-Trimethoxy-3-piperidyl-2,2′-binaphthalene-1,1′,4,4′-tetrone exhibited the highest binding affinity for Actin like protein (−7.6 kcal/mol), β-1,3 glucan synthase (−7.7 kcal/mol), Pectinesterase (−4.2 kcal/mol) and Polygalacturonase (−6.5 kcal/mol) protein targets of R. solani compared to the commercial fungicide carbendazim. In vivo experiments also proved the efficacy of B. velezensis B13 in suppressing rice sheath blight disease reduction upto 16.8± 0.2 besides enhancing the growth of the plant. Furthermore, B. velezensis B13 upregulated the expression of rice transcription factors and defense genes, viz., WRKY, PR1, PAL, LOX, FLS2 and CERK1, by several folds related to the inoculated and healthy control, leading to the suppression of R. solani. Our results suggest that B. velezensis (B13) could be a potential candidate for developing a bioconsortia for the sustainable management of rice sheath blight.